2021
DOI: 10.1007/s10608-020-10180-7
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation Bias Across Body Dysmorphic, Social Anxiety and Generalized Anxiety Disorder—A Multilevel, Diffusion Model Account

Abstract: Background Interpretation biases are suggested to be transdiagnostic phenomena, but have rarely been compared across different disorders and current concerns. Methods We investigated explicit, decision-based, and more implicit, reaction time-based interpretation bias in individuals with body dysmorphic disorder (BDD; N = 29), social anxiety disorder (SAD; N = 36), generalized anxiety disorder (GAD; N = 22), and non-clinical controls (NC; N = 32), using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 91 publications
(119 reference statements)
1
5
0
Order By: Relevance
“…Several studies have suggested that appearance anxiety can positively predict SAD among normal samples, and even among eating disorder samples ( 8 , 13 , 14 ). In turn, SAD symptoms also predict appearance anxiety and other body image disorders ( 13 , 15 ). Furthermore, appearance anxiety is highly correlated with eating disorders such as anorexia nervosa and bulimia nervosa ( 16 ), and appearance-related comments can increase appearance anxiety and directly or indirectly affect eating disorders ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that appearance anxiety can positively predict SAD among normal samples, and even among eating disorder samples ( 8 , 13 , 14 ). In turn, SAD symptoms also predict appearance anxiety and other body image disorders ( 13 , 15 ). Furthermore, appearance anxiety is highly correlated with eating disorders such as anorexia nervosa and bulimia nervosa ( 16 ), and appearance-related comments can increase appearance anxiety and directly or indirectly affect eating disorders ( 17 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, perceived stigmatization may lead to enhanced appearance concerns. However, body dysmorphic disorder is common in skin conditions ( 14 ) and one of its core features is the continuous awareness of others looking at appearance defects, which could lead to misinterpretation of ambiguous social situations ( 33 ) and thereby increased reporting of perceived stigmatization. Similarly, higher levels of distress and presence of suicidal ideation may lead to a negative evaluation of social interactions ( 34 ), resulting in greater self-reported perceived stigmatization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they believe others to be critical (Buhlmann, et al, 2006) and fear rejection (Kelly et al, 2014). Thus, individuals with BDD are regularly confronted with situations in which they are biased to negative and appearance-related interpretations (Buhlmann et al, 2002; Dietel et al, 2021). Due to the overimportance of appearance for the self (Veale, 2004), it seems plausible that low self-esteem fosters maladaptive beliefs.…”
Section: Discussionmentioning
confidence: 99%